Anti-diabetic potential of crude extracts of medicinal plants used as substitutes for Swertia chirayita using in vitro assays - Phoboo, Susanna; Bhowmik, Prasanta C; Jha, Pramod Kumar; Shetty, Kalidas (Botanica Orientalis: Journal of Plant Science, 2011)
Swertia chirayita is a highly traded medicinal plant of Nepal widely used for its anti-diabetic potential. In this study, two herbs (Swertia nervosa and Andrographis paniculata) often used as adulterants and substitutes of Swertia chirayita were analyzed for their antioxidant activity, α-glucosidase inhibitory potential and total phenolic content and compared with that of Swertia chirayita. Aqueous and 12% ethanolic extracts of the three herbs showed moderate to high antioxidant activity and moderate α-glucosidase inhibitory potential. HPLC/ DAD revealed the presence of swertiamarin and mangiferin in all the Swertia species, while Andrographis paniculata contained cinnamates such as cinnamic acid, p-coumaric acid and chlorogenic acid. The antioxidant activity and α-glucosidase inhibitory potential was evident in the two herbs indicating their relevance as substitutes for Swertia chirayita for potential early stage management of type-2 diabetes and related complications. Key-words: Andrographis paniculata; antioxidant activity; cinnamates; mangiferin; Swertia nervosa; swertiamarin; α-glucosidase; type-2 diabetes. DOI: 10.3126/botor.v7i0.4373 Botanica Orientalis – Journal of Plant Science (2010) 7: 48-55